Ossicular Chain Status in Adults with Chronic Otitis Media Mucosal at a Tertiary Referral Hospital in Nepal - KC, Sarita; Bista, Ranishma; Bhattarai, Sriya; Dutta, Vijay Bhushan (Med Phoenix, 2022)
Introduction Chronic Otitis Media (COM) is a common condition characterized by perforation of the tympanic membrane and inflammation of middle ear cleft mucosal lining for at least 2-6 weeks. This study was carried out to find out the status of the middle ear ossicles in patients with COM mucosal and to correlate with clinical parameters. Materials and Methods This retrospective clinical study comprises 106 myringoplasty patients at the department of ENT, Shree Birendra Hospital. Their preoperative PTA, four frequencies (500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz) Air Conduction Thresholds (ACT), and Air Bone Gap (ABG) were recorded. Ossicular chain integrity and mobility evaluated intraoperatively were noted. Ossicular chain status was analyzed with ACT and ABG. Results The ossicles were intact and mobile in 91.5%, either fixed/ restricted or disrupted in 8.5%. Mean ACT and ABG comparisons in intact and ossicular chain defect groups were statistically significant. Frequency-specific ACT at all four frequencies and ABG except at 4000 Hz in the two groups were also statistically significant to predict the ossicular involvement. The group with ossicular defect had moderate to severe Conductive Hearing Loss (CHL). Conclusion Mean as well as frequency-specific ACT and ABG can be considered as a potential preoperative predictor for ossicular chain status in COM mucosal.